Socialization and Social Capital in Online Doctoral Programs - Brett, Clare; Lee, Kyungmee; Oztok, Murat (Proceedings of the International Conference on Networked Learning, 2016)
Online doctoral programs are gaining in popularity, both among students and institutions. However, research to date on the effectiveness and popularity of such programs has looked largely at either measures of student satisfaction or of administrative effectiveness and design. Further, previous research has also tended to focus on the early part of doctoral study, particularly coursework. This mixed method study, conducted on three different programs within in a department of educational research in one university in UK will contribute to the literature in two important ways. First, it will look specifically on current and recently graduated student experiences from of the thesis component of the doctoral program using a demographic and experiential survey and following up with more in depth interviews to better understand students’ motivation and goals for enrolling in their program and what kinds of academic experiences and knowledge they both bring to, and receive from, their program. Second, we will analyse the data through two lenses, that of academic socialization to help identify how academic identity changes over time, and that of social capital to help us understand the individual trajectories of students through their programs. Results will contribute both theoretically and practically to our understanding of student experience of the thesis process in online doctoral programs.